2017
DOI: 10.1038/s41598-017-00085-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Hyaluronic Acid in Lymphedematous Tissue Alleviates Fibrogenesis via TH1 Cell-Mediated Cytokine Expression

Abstract: Although surgery and radiation are beneficial for treating cancer, they can also lead to malfunctions of the lymphatic system such as secondary lymphedema. This abnormality of the lymphatic system is characterized by severe swelling, adipogenesis, inflammation, and fibrosis in the lymphedematous region. Moreover, the proliferation of fibrotic tissue in the lymphedematous region generates edema that is no longer spontaneously reversible. No treatment for fibrosis has been validated in patients with lymphedema. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…However, enhanced defense response against bacteria in Ymt compared to Omt is compatible with an increased capacity to resist to the attack of pathogenic gut bacteria, which could provide the basis for longer life span. Remarkably, hyaluronic acid metabolism, altered between the experimental groups receiving young and old gut contents, has been associated with increased inflammation, deregulated immune response and risk for cancer ( Cho et al, 2017 ; Tian et al, 2013 ), all of which could provide the basis for life span modulation. Finally, we provide a dataset that allows to associating OTU levels in individual fish to intestinal transcripts, enabling to investigate on how GM and host gene expression are mutually regulated.…”
Section: Resultsmentioning
confidence: 99%
“…However, enhanced defense response against bacteria in Ymt compared to Omt is compatible with an increased capacity to resist to the attack of pathogenic gut bacteria, which could provide the basis for longer life span. Remarkably, hyaluronic acid metabolism, altered between the experimental groups receiving young and old gut contents, has been associated with increased inflammation, deregulated immune response and risk for cancer ( Cho et al, 2017 ; Tian et al, 2013 ), all of which could provide the basis for life span modulation. Finally, we provide a dataset that allows to associating OTU levels in individual fish to intestinal transcripts, enabling to investigate on how GM and host gene expression are mutually regulated.…”
Section: Resultsmentioning
confidence: 99%
“…Th2 cells have been shown to promote tissue fibrosis in lymphedema through production of TGF-β (118). A recent study showed that hyaluronidase was able to reverse tissue fibrosis in a hind limb postsurgical lymphedema model through a mechanism that promotes Th1 but diminishes Th2 cell activity (138). Together, these studies suggest that Th2 cells are essential in promoting tissue fibrosis in postsurgical lymphedema.…”
Section: Lymphedemamentioning
confidence: 99%
“…Pulmonary lymphatics collect excess protein‐rich fluid that extravasates from blood vessels, and transport it back into the blood circulation . Failure of the lymphatic drainage system causes sustained tissue inflammation and abnormal wound healing, such as fibrosis and pleuritis . In addition, some reports have suggested that lymphatic vessel proliferation can induce fibrogenesis in IPF/UIP .…”
Section: Discussionmentioning
confidence: 99%